Técnicas de produção de gás como preditoras do valor nutricional de dietas e extrato de Poincianella pyramidalis Tul. como modulador da fermentação ruminal. - Suassuna, Juraci Marcos Alves (2020)
This study consisted of two experiments. In the first, the aim was to compare the gas production profiles and nutrient degradability of diets using two in vitro gas production techniques, automatic and semi-automatic. For this, a randomized block design in a 2 × 2 factorial arrangement was adopted, with two diets with different proportions of non-fibrous carbohydrates (NFC), (low NFC vs high NFC) and two gas production techniques (automatic vs semi-automatic), with four replicates. The blocks represented three in vitro runs. Gas production from the fermentation of fibrous carbohydrates (Vf2) was 22% higher in the automatic technique compared to the semiautomatic. There was interaction for the estimation of the total gas production (Vt) at 72 hours of incubation (P = 0.034), where in the automatic technique the production was higher than the semi-automatic technique, for high and low NFC diet. Gas production from NFC (Vf1) showed a positive correlation of high magnitude (r = 0.94; R 2 = 0.87), while for Vf2 a strong positive correlation was observed (r = 0.702; R2 = 0.47). There was a positive correlation of high magnitude (r = 0.96; R2 = 0.93) between the techniques, for the total gas production (Vt). There was greater degradability of dry matter (DM) (+ 3.8%), organic matter (OM) (+ 3.3%). In both diets, the degradability of crude protein (CP) was greater in the semiautomatic technique (P < 0.0001). The high NFC diet resulted in lower pH and lower N-NH3 in the incubation medium, compared to the low NFC diet, while the degradability of DM, OM and CP increased. The automatic and semi-automatic techniques estimated the kinetic parameters and the profiles of total gas production similarly, demonstrating the potential of both techniques for assessing the nutritional value of diets with different proportions of NFC. In the second study, the aim of this study was to evaluate the effect of including Poincianella pyramidalis (Tul.) L. P. Queiroz extract on gas production kinetics and the degradability of diets with different proportions of non-fibrous carbohydrates (NFC). A randomized block design in a 4 × 2 factorial arrangement was adopted, with four levels of extract inclusion [0, 3, 6, 9% of dry matter (DM)], two diets (low NFC and high NFC), and three replicates. The blocks represented two in vitro runs. In the high NFC diet, protein degradability was linearly reduced with increase of P. pyramidalis extract levels (P < 0,05). There was a quadratic effect (P = 0.0009) of P. pyramidalis extract on the fiber in neutral detergent degradability, with a maximum point estimated at 609.7 g/kg DM for the level of 2.16%. There was a linear reduction in pH (P = 0.0001), N-NH3 (P = 0.0002), acetate molar proportion (P = 0.0363) and the acetate: propionate ratio (P = 0.0118) with increase of extract levels. The low NFC diet resulted in a higher pH value, N-NH3, short chain fatty acids and molar proportion of acetate compared to the high NFC diet. The addition of P. pyramidalis extract increased linearly (P = 0.0419) the average gas production (ml/g OM). The high NFC diet resulted in greater volume (ml/g DM) and higher gas production rates (P < 0.0001) and greater lag time (P = 0.0290) compared to the low NFC diet. The inclusion of P. pyramidalis extract in both diets modified the rumen fermentation pattern, favoring the production of propionate and reducing acetate. The effect of the extract on the degradability of crude protein was more impressive in the high NFC diet, with a reduction of crude protein degradability with increasing levels of P. pyramidalis. The neutral detergent fiber degradability was favored up to the level of 2.16% of extract and, from that level decreased.